Apollon: a deoxyribozyme that generates a yellow product - Volek, Martin; Kurfürst, Jaroslav; Kožíšek, Milan; Srb, Pavel; Veverka, Václav; Curtis, Edward A (Nucleic acids research, 2024)
Colorimetric assays in which the color of a solution changes in the presence of an input provide a simple and inexpensive way to monitor experimental readouts. In this study we used in vitro selection to identify a self-phosphorylating kinase deoxyribozyme that produces a colorimetric signal by converting the colorless substrate pNPP into the yellow product pNP. The minimized catalytic core, sequence requirements, secondary structure, and buffer requirements of this deoxyribozyme, which we named Apollon, were characterized using a variety of techniques including reselection experiments, high-throughput sequencing, comparative analysis, biochemical activity assays, and NMR. A bimolecular version of Apollon catalyzed multiple turnover phosphorylation and amplified the colorimetric signal. Engineered versions of Apollon could detect oligonucleotides with specific sequences as well as several different types of nucleases in homogenous assays that can be performed in a single tube without the need for washes or purifications. We anticipate that Apollon will be particularly useful to reduce costs in high-throughput screens and for applications in which specialized equipment is not available.
Keywords: Oligonucleotides; Substrate Specificity; kolorimetrie; High-Throughput Nucleotide Sequencing; Nucleic Acid Conformation; DNA, Catalytic; Phosphorylation; konformace nukleové kyseliny; oligonukleotidy; Colorimetry; DNA katalytická; substrátová specifita; vysoce účinné nukleotidové sekvenování; fosforylace